A Study on Adoption of Internet Banking among Customers of Public and Private Sector Banks in North Gujarat: Exploring Factors Influencing Internet Banking Adoption in North Gujarat (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of this study is to understand that which factors significantly influencing the adoption of the internet banking among the customers of public sector bank and private sector banks in North Gujarat. Adoption of internet banking by the consumers of the banking sectors are increasing in the present era. Under the current study researchers had reviewed the past literatures in the field of the adoption of the internet banking among the consumers of banks around the world. Also, it can be seen that there are various studies related to adoption of the internet banking has been done in India. After the review of literature on hand, the data was collected though questionnaires from various people over the regions in the North Gujarat. After the data analysis researchers derived the results that the factors significantly influencing adoption of internet banking in North Gujarat are perceived usefulness, perceived ease of use, awareness of internet banking, quality of internet connection and computer self-efficacy. The attitude toward the use of internet banking and perceived usefulness can be used to predict the intention to use internet banking by users.